Risks of the use of androgen anabolic steroids in sports (Research, Society and Development, 2022)
Anabolic androgenic steroids are synthetic substances produced from the male hormone testosterone. In recent decades these drugs have been used by gym goers. However, indiscriminate use has taken a large proportion, thus leading to a concern due to its side effects, often irreversible, that can occur. To carry out this research, a survey of scientific articles was carried out in the Scielo, PubMed, BVS, Lilacs and Google Scholar databases, in which 81 bibliographic materials were obtained, of which 20 were selected, between the years 2000 and 2021. Information obtained in this research reveals that in recent years there has been a significant increase in the use of anabolic androgenic steroids by athletes in order to increase their physical performance or just for aesthetics, thus causing some side effects. Therefore, the present study aims to analyze the risks of using androgenic anabolic steroids in sports.